Analysis of the Impact of Social Media as a Learning Tool in Language Subjects - Usup, Usup; Purwaningsih, Dewi Ismu (Journal of Computer Science Advancements, 2024)
Integrating digital platforms in education has seen a notable shift in incorporating social media to enhance learning experiences. In language education, social media platforms offer interactive, engaging environments that can improve language acquisition and proficiency. This study aims to analyze the effectiveness of social media as a learning tool in language subjects, focusing on its impact on student engagement and language proficiency. A mixed-method approach was utilized, combining quantitative surveys and qualitative interviews with 200 high school students who used social media for language learning. The quantitative data were analyzed using statistical techniques to measure engagement and proficiency, while thematic analysis was applied to the qualitative data to explore student perceptions and experiences. The findings indicate that students using social media for language learning reported higher levels of engagement and demonstrated significant improvement in language proficiency compared to those using traditional methods. The interactive and collaborative nature of social media was found to facilitate more practical language use, which is critical for learning. Social media can significantly enhance student engagement and language proficiency when effectively integrated into language learning curricula. Educators are encouraged to explore and utilize social media platforms to create more dynamic and responsive language learning environments.